Expression of p38MAPK and its regulation of apoptosis under high temperature stress in the razor clam Sinonovacula constricta. Issue 122 (March 2022) - Wang, Yizhen; Han, Yuting; Wang, Yanhui; Lv, Min; Li, Yifeng; Niu, Donghong
Abstract: p38MAPK is a key branch of the MAPK (mitogen-activated protein kinase) pathway that plays an important role in physiological processes such as apoptosis, cell proliferation and growth. In this experiment, we screened and identified one p38MAPK gene in the razor clam Sinonovacula constricta, which encoded 359 amino acids and was widely expressed in various adult tissues. After 24 h of high temperature stress at 34 °C, the transcript expression of p38MAPK showed significant changes in all tested tissues. In particular in the gill and hepatopancreas tissues, where the expression increased 1.81 and 7.83 times compared with the control group, respectively ( P < 0.01 ). Furthermore, we examined the expression of the apoptosis suppressor gene Bcl-2 and pro-apoptosis gene Bax by knock-down of p38MAPK with dsRNA interference in the gill and hepatopancreas tissues. The obvious up-regulation expression of Bcl-2 and significant suppression of Bax were observed, respectively ( P < 0.01 ). Moreover, the TUNEL staining technique was used to detect apoptosis before and after interference. The degree of apoptosis in the gill and hepatopancreas tissues was reduced after interference with p38MAPK, and the ROS content was significantly reduced ( P < 0.01 ). The results suggested that p38MAPK had a regulatory role in the heat tolerance of razor clams. Highlights: p38MAPK expression was up-regulated in gill and hepatopancreas at high temperatures. Bcl-2 / Bax ratio in gill and hepatopancreas decreased under high temperature stress. Knockdown of p38MAPK increased the ratio of the pathway gene Bcl-2 / Bax. Knockdown of p38MAPK inhibited apoptosis in gill and hepatopancreas tissues.